Development of e-logbook System for Undergraduate Students of the Faculty of Arts and Social Science (FAS), University Tun Abdul Rahman (UTAR) - Lee, Jet; Norhamreeza Abdul Hamid (Applied Information Technology And Computer Science, 2022)
The e-logbook System is a web-based system and was specially developed for year 3 students of the Faculty of Arts and Social Sciences (FAS) at University Tun Abdul Rahman (UTAR). Project users are students, supervisors, and coordinators. This project aims to assist year 3 students while starting and creating final year projects. Students will be more comfortable and systematic to do weekly activities report after discussion with the supervisor and be informed of the information announced. The coordinator can easily gather all Year 3 pupils and upload important information. The project is developed based on the Prototype model where improvements are made from time to time. The software used to build the e-PSM system is Brackets, Notepad, and XAMPP. Additionally, phpMyAdmin is used for system databases. There are four modules in the e-logbook System, namely the login module, the user registration module, the activity report generator module, and the student group assignment to the supervisor module. The login module is used by students, supervisors, and coordinators by entering a matrix number or lecturer ID and password. The user registration module is only open to coordinators to register a new account by entering the lecturer ID, email, and password. The activity report generator module is only made by students to record the results of weekly discussions with supervisors and weekly activity reports are sent to supervisors and coordinators. The student group assignment module to the supervisor is created by the coordinator to enter student and supervisor information. The system tests that will be conducted on users are system function tests in terms of storing and manipulating user details data, system function tests in terms of storing and manipulating report data, and system function tests in terms of storing and manipulating notification data. Based on the test through the test plan, shows that the actual output is the same as the expected output. As for the user acceptance test, most respondents felt very satisfied and satisfied with the system.